New approach of Cultural Property Fire Fighting System with Building Information Modeling (BIM) and Drone - Eom, Shinjo; Kim, Sangchul (International Journal of Engineering and Technology, 2018)
Background/Objectives: Preventing the fire of cultural properties is a very important issue, but it is difficult to suppress the fire early due to the wooden structure of cultural properties.Methods/Statistical analysis: The research team proposed a monitoring system using Building Information Modeling (BIM) and a fire suppression system using drone. It is constructed a cultural information integration model (BIM) which is constructed by including attribute and physical information based on laser scanning information, so could obtain the object's attributes information into BIM data to respond to cultural assets fire response system.Findings: From literature review, there is no fire prevention standard considering its special nature based on the Cultural Properties Protection Act and the possibility of fire due to the deterioration of electric facilities. Therefore, the research team proposed a fire monitoring system with a drone that was connected with the fire detection system that is described as development of internet of things (IoT) converged real-time fire monitoring system based on the integrated building information model (BIM) with infrared heat-seeking sensor camera and development of robotic fire fighting device and/or drone fire system that enables optimal fire response by XYZ coordinate of fire point that is linked to real-time fire monitoring system. Through this, the research team could get an advantage that fire can be extinguished in early by integrating fire position information received from a fire monitoring system connected with fire detection sensor based on drone.Improvements/Applications: The proposed system could lead overall facility layout plan with virtual simulation system, reduce damages by hydraulic pressure. Finally, precise fire response and minimal damages were expected in the event of a cultural property fire.Â Â